The The Use of Magboard in Improving the Writing Creativity at Kangaroo School - Devi Oktasari (Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to describe (1) the use of a Magboard in improving English writing creativity at Kangaroo School, and (2) the benefits of Magborard in improving English writing creativity at Kangaroo School. This research was classified into Classroom Action Research (CAR). The subject of this research was Kangaroo school. In conducting the research, the Kangaroo's teachers and supervisors were invited to provide feedback to the lesson plan made. Interview also conducted with the teacher as a collaborator to gain the data about the benefits of the Magboard. The results showed that various tasks using Magboard can be conducted in observing and experimenting stages. Based on the reflection, the researcher changed and used Plan-Do-Review as the final teaching and learning procedures. In each stage, Magboard can also be implemented on various tasks. Magboard benefited as 1) being the relevant media; 2) attract the students' interest, attention and enthusiast; 3) facilitating the teacher, and 4) providing new idea for the teacher. Keywords: Magnetic Board, English for children, writing, creativity.